1999
DOI: 10.1021/bp990090f
|View full text |Cite
|
Sign up to set email alerts
|

Precursor and Cofactor as a Check Valve for Cephamycin Biosynthesis in Streptomyces clavuligerus

Abstract: The biosynthesis of secondary metabolites is closely linked to primary metabolism via the supply of precursors, cofactors, and cellular energy. The availability of these precursors and cofactors can potentially be rate-limiting for secondary metabolism. A combined experimental and kinetic modeling approach was used to examine the regulation of flux in the cephamycin biosynthetic pathway in Streptomyces clavuligerus. The kinetic parameters of lysine 6-aminotransferase (LAT), the first enzyme leading to cephamyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…The LAT activity seemed to be independent of the initial lysine concentration in the culture media, presenting the same level of expression in 24 h of fermentation. These results were consistent with the previous data from the literature which demonstrated that LAT was preferably synthesized in the exponential growth phase and presented higher activity at this stage of the process (Khethan et al 1999). However, in addition to playing the role of positive regulator of the LAT expression, it was observed that the excess of lysine in the medium, initially containing 100 mM of amino acid, supported the maintenance of the LAT activity at slightly higher values along the fermentation, when compared with those observed in 10 mM supplemented medium.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The LAT activity seemed to be independent of the initial lysine concentration in the culture media, presenting the same level of expression in 24 h of fermentation. These results were consistent with the previous data from the literature which demonstrated that LAT was preferably synthesized in the exponential growth phase and presented higher activity at this stage of the process (Khethan et al 1999). However, in addition to playing the role of positive regulator of the LAT expression, it was observed that the excess of lysine in the medium, initially containing 100 mM of amino acid, supported the maintenance of the LAT activity at slightly higher values along the fermentation, when compared with those observed in 10 mM supplemented medium.…”
Section: Discussionsupporting
confidence: 93%
“…Lysine was determined by the post column orthophthaldialdehyde (OPA) derivatization method. Enzymatic activity of lysine ε-aminotransferase (LAT) and cadaverine aminotransferase (CAT) was determined according to Khethan et al (1999).…”
Section: Methodsmentioning
confidence: 99%
“…Although a wide variety of microorganisms synthesize antibiotics, the majority of the clinically useful compounds are produced by actinomycetes (Khetan et al, 1999). Among these organisms, members of the genus Streptomyces are responsible for the production of about 80% of the known secondary metabolites, especially antibiotics (Challis and Hopwood, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing these features, a number of studies have demonstrated the value of GFP as a reporter of gene expression (Chalfie et al, 1994 ;Kremer et al, 1995) and protein localization (Lewis & Errington, 1996 ;Webb et al, 1995 ;Yoon & Golden, 1998) in bacteria. Recent work in our laboratory and that of others has also illustrated the use of various mutants of GFP in deciphering expression patterns in Streptomyces mycelia (Han et al, 1999 ;Khetan, 1998 ;Sun et al, 1999).…”
Section: Introductionmentioning
confidence: 97%